Visualizing youth sports specialization and injury risk: A novel application of swimmer plots - Julie Agel; Nicholas Edwards; Bradley Nelson; Todd Rockwood (PLoS ONE, 2026)
Background As research on sport participation in youth and the impact of sport specialization on injury increases, the value of a standardization of data variables and an easily interpretable way of visualizing the data will be demonstrated with improved quality and comparability of future findings. Purpose Using simulated sport participation data from the perspectives of chronological age and years of participation, the utility and flexibility provided by swimmer plots is a novel method for visualization of data to assess the impact of single versus multiple sport participation on the occurrence of injury. Methods Using recall survey data, a simulated dataset based on chronological age as well as years of participation was created to allow for differing visualizations of the impact of single vs multiple sport participation on the occurrence of injury using swimmer plots. Results Characterization and presentation of sports history are deceptively complex and the reliance on tabular and simple graphics fail to provide a comprehensive picture. Collecting a core data set, allowing for multiple denominators such as chronological age and years of participation along with using swimmer plots as an effective means of visually presenting the data allow for a more robust and multi-faceted approach to the understanding of the impact of youth early sport specialization on injury risk. Demonstrated are examples of injury occurrence as it relates to chronological age of participation as well as years of participation. Figures demonstrating differences in injury rates based on number of sports participated in at various ages are also provided. Conclusion Swimmer plots allow for visualization of data from multiple perspectives which facilitates a comprehensive understanding of the complex, overlapping factors potentially impacting injury in youth sports. Visualizing more than one perspective allows for a more complete picture of the factors involved.